LIFE WORLDS AND REGIONAL IDENTITY AS AN ASSOCIATED SCIENTIFIC PROBLEMS - G. F. Romashkina; V. A. Davydenko (Модернизация, инновация, развитие, 2017)
The article deals with the problems of the life-world and regional identity, as a conjugate scientific contexts. The authors reviewed the scientific tradition of social phenomenology, epistemology, interpretive sociology, sociology of action and anthropology. Presents the scientific research, which set a goal to recognize and problematize particular meanings of social life of regional communities, socio-cultural meanings of regional life, taken from the perspective of the concepts of social reality, the life of the world, personal picture of the world, collective, settlement and territorial identity, trust, understood as a kind of mental model semantic structures. The novelty of the research is to try to joints on concrete empirical evidence of cognitive and models competing scientific currents: phenomenology and sociology of action. The methodology includes an analysis of the results of the mass of concrete sociological research carried out in one of the most prosperous regions of Russia (Tyumen region). Modernization (colonization) of the life of the world (in terms of Habermas) rationalist (bureaucratic) structures clearly demonstrated the rich empirical material involving the correlation analysis methods. The contradictions between the system (the economy and the state) and the lifeworld (private and public spheres), which crystallized around the social role and false demonstration of communicative relationship that occurs in Russia today. Manifested most strongly rooted in community life. The authors demonstrate how the variability of "social peace" is off set (or compete) with resistance "subjective world". The observed trajectory demonstrate movement towards the modernization of the social world, but this is not enough to go to a diff erent society, a modern path of historical development.